Ajuste y reclasificación de PPYE en la empresa constructora el Camino S.A. del año 2019. - Coyago Jimenez, Jessica Andrea (My University, 2020)
The main objective of the present investigation is to propose the adjustment sheet of the material error of machinery and equipment and vehicles, transport equipment and mobile equipment in the Company Constructora El Camino SA of the year 2019. Since, its preparation is important to present information Reasonable and transparent financial compliance with financial and accounting standards, committed to efficient decision making. The methodology used for the resolution of the case study is documentary research through scientific articles from various journals approved in Article 30 of the Utmach Degree Guide. Therefore, the properties, plant and equipment are the accounts detected by the adjustments developed, in the Income Statement and Financial Situation; It is noted that the usual errors of the accountants is the erroneous accounting record forgetting the nature and function of the good. In this sense, the accounts involved in the adjustments are accumulated depreciation recognizing that their useful life at the beginning was calculated for 10 years and with the modifications represents only 5 years according to the international accounting norm and international financial information regulations; the components of vehicle, transport equipment and mobile mobile equipment, participation of workers and income tax payable. At the same time, the audit reclassification established by the auditor is only presented in case of an erroneous recognition of an account and that does not produce a modification on the account group.
El objetivo principal de la presente investigación es proponer la hoja de ajuste del error material de maquinaria y equipo y vehículos, equipo de transporte y equipo caminero móvil en la Empresa Constructora El Camino S.A. del año 2019. Puesto que, es importante su elaboración para presentar información financiera razonable y transparente dando cumplimiento a las Normativas financieras y contables, llevando a la toma decisiones eficientes. La metodología utilizada para la resolución del caso práctico, es la investigación documental a través de artículos científicos de diversas revistas aprobadas en el Artículo 30 de la Guía de Titulación de la Utmach. Por lo tanto, las propiedades, planta y equipo se ven las cuentas afectadas por los ajustes desarrollados, en los Estados de Resultados y de Situación financiera; se señala, que los errores habituales de los contadores es el registro erróneo contable olvidando la naturaleza y la función del bien. En este sentido, las cuentas involucradas por los ajustes, se encuentran la depreciación acumulada reconociendo que su vida útil al inicio fue calculada por 10 años y con las modificaciones representa solo 5 años conforme la norma internacional de contabilidad y normativa internacional de información financiera; los componentes de vehículo, equipo de transporte y equipo caminero móvil, participación de trabajadores y el impuesto a la renta por pagar. A la vez, la reclasificación de auditoria establecido por el auditor, solo se presentan en caso de reconocimiento erróneas de una cuenta y que no produce una modificación sobre el grupo de la cuenta.
Keywords: AUDITORÍA; PROPIEDAD PLANTA Y EQUIPO; HOJA DE AJUSTE Y RECLASIFICACIÓN DE AUDITORÍA; MAQUINARIA Y EQUIPO; EQUIPO CAMINERO MÓVIL